Предмет: Алгебра,
автор: TMR
Упростить выражение:
Ответ:
Ответы
Автор ответа:
0
Решение:
((a-b)^2(sqrt(a+sqrt(b)+(a-b)(a+b)(sqrt(a)-sqrt(b))/((a-b)(a+b+sqrt(ab))=
=((a-b)(sqrt(a)+sqrt(b))+(a+b)(sqrt(a)-sqrt(b))/(a+b+sqrt(ab))=
=2(a^(3/2)-b^(3/2))/(a+b+sqrt(ab))=2(sqrt(a)-sqrt(b)).
Автор ответа:
0
ответ во вложении...............................
Приложения:
Похожие вопросы
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Қазақ тiлi,
автор: zjangalijaksilik
Предмет: Физика,
автор: fevralskayasofya
Предмет: Физика,
автор: sain1998